Dynamics of Ethylene Production in Response to Compatible Nod Factor. Issue 2 (29th November 2017) - Reid, Dugald; Liu, Huijun; Kelly, Simon; Kawaharada, Yasuyuki; Mun, Terry; Andersen, Stig U.; Desbrosses, Guilhem; Stougaard, Jens
Abstract : The host plant Lotus japonicus produces ethylene in response to compatible Nod-factor to regulate nitrogen-fixing symbiosis. Abstract: Establishment of symbiotic nitrogen-fixation in legumes is regulated by the plant hormone ethylene, but it has remained unclear whether and how its biosynthesis is regulated by the symbiotic pathway. We established a sensitive ethylene detection system for Lotus japonicus and found that ethylene production increased as early as 6 hours after inoculation with Mesorhizobium loti . This ethylene response was dependent on Nod factor production by compatible rhizobia. Analyses of nodulation mutants showed that perception of Nod factor was required for ethylene emission, while downstream transcription factors including CYCLOPS, NIN, and ERN1 were not required for this response. Activation of the nodulation signaling pathway in spontaneously nodulating mutants was also sufficient to elevate ethylene production. Ethylene signaling is controlled by EIN2, which is duplicated in L. japonicus . We obtained a L. japonicus Ljein2a Ljein2b double mutant that exhibits complete ethylene insensitivity and confirms that these two genes act redundantly in ethylene signaling. Consistent with this redundancy, both LjEin2a and LjEin2b are required for negative regulation of nodulation and Ljein2a Ljein2b double mutants are hypernodulating and hyperinfected. We also identified an unexpected role for ethylene in the onset of nitrogen fixation, with the Ljein2a Ljein2b double mutant showing severely reduced nitrogen fixation. These results demonstrate that ethylene production is an early and sustained nodulation response that acts at multiple stages to regulate infection, nodule organogenesis, and nitrogen fixation in L. japonicus .